Analisis Kelayakan Teknis Komoditas Rumput Laut Berbasis Parameter Oceanografi Di Kecamatan Petasia Timur, Kabupaten Morowali - Zakirah Raihani Ya’la; Muh. Ahlil Gunawan; Nasmia; Eka Rosyida (Universitas PGRI Silampari, 2025)
North Morowali Regency is one of the regions in Central Sulawesi Province that has prospects for developing seaweed aquaculture activities. The study aims to analyze the technical and financial feasibility of seaweed cultivation in Petasia Timur District. The data collection method is carried out by observation and interviews covering the technical and financial aspects of seaweed cultivation. North Morowali Regency has a fairly large cultivation location, especially in East Petasia District. However, in recent years there has been a decrease in production due to problems with the quality of sea water. This study aims to analyze the technical feasibility of seaweed cultivation. The results showed that the water quality parameter data obtained from 3 sampling villages in East Petasia Timur District, namely Ungkea Village with a score of 53,3%, Bungintimbe Village 55,5%, and Towara Pantai Village 53,3%. In general, the value is below the range of water feasibility, so that the cultivation sites in the three sampling villages are said to be less suitable for seaweed growth.